2017
DOI: 10.1016/j.epsl.2017.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of melt interconnectivity and electrical conductivity in the upper mantle

Abstract: International audienceThe presence of a small fraction of basaltic melt is a potential explanation for mantle electrical conductivity anomalies detected near the top of the oceanic asthenosphere. The interpretation of magnetotelluric profiles in terms of the nature and proportion of melt, however, relies on mathematical models that have not been experimentally tested at realistically low melt fractions (<0.01). In order to address this, we have performed in situ electrical conductivity measurements on partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 66 publications
4
40
0
1
Order By: Relevance
“…To explain the anomalous high conductivity in geophysical field observations of magnetotelluric and geomagnetic deep sounding data, many in situ laboratory-based high-pressure conductivity studies have been reported for relevant minerals and rocks in recent decades. Some potential explanations for high conductivity anomalies in the deep interior of the Earth and other planets have been proposed such as the hydrogen-bearing of nominally anhydrous minerals [1,2], dehydration of minerals [3,4], partial melting [5,6], dehydrogenation of minerals [7], anisotropy [8], and the presence of an interconnected high conductivity impurity phase [9].…”
Section: Introductionmentioning
confidence: 99%
“…To explain the anomalous high conductivity in geophysical field observations of magnetotelluric and geomagnetic deep sounding data, many in situ laboratory-based high-pressure conductivity studies have been reported for relevant minerals and rocks in recent decades. Some potential explanations for high conductivity anomalies in the deep interior of the Earth and other planets have been proposed such as the hydrogen-bearing of nominally anhydrous minerals [1,2], dehydration of minerals [3,4], partial melting [5,6], dehydrogenation of minerals [7], anisotropy [8], and the presence of an interconnected high conductivity impurity phase [9].…”
Section: Introductionmentioning
confidence: 99%
“…6). In addition, when hydrous ε-FeOOH meets hotter regions in the mantle, it causes dehydration melting that would further boost the overall transport properties 63 . We therefore suggest that those localized domains with topped 10 2 S/m EC may have incorporated higher concentration of ε-FeOOH, or the enrichment of other superior EC components.…”
Section: Discussionmentioning
confidence: 99%
“…JONES et al , 2011FULLEA 2017), továbbá a kis mennyiségben jelen lévő mafikus (pl. NI et al 2011, MILLER et al 2015, LAUMONIER et al 2017 vagy karbonátos olvadék jelenlétét is (SIFRÉ et al 2014).…”
Section: Fajlagos Vezetőképességunclassified